Organizing principles in the Spanish Education Inspectorate: strengths and weaknesses - Tomás Secadura Navarro (ADIDE Federación, 2008)
In Spain, it is autonomic authorities who are charged with organizing their own education inspectorates. At present, an analysis of the legal framework in effect within all eighteen administrations (including the central or state administration) reveals the existence of organizing criteria and principles which are common to all of them, but also the presence of clear differences and singularities. The goal of the present work is to analyze and describe the eleven organizing principles shared by each of the inspectorates, which define their structure. In so doing, we are convinced we will also be describing what we think are their most significant strengths and weaknesses. These eleven structuring or guiding principles are: unity, homogeneity, territoriality, professionalism, hierarchydependency, planning, team work, coordination, specialization, standardization of inspecting activity and result assessment. Our analysis ends by stating the need of a change in the existing inspectorate model, in a search for a field of our own, of greater quality and efficacy, in order to be able to deal with the complexity of the school system, both present and future.